Magnetic Behavior of Co2+-Doped NiFe2O4 Nanoparticles with Single-Phase Spinel Structure - Fatemeh Vahedrouz; Mehdi Alizadeh; Abbas Bahrami; Farnaz Heidari Laybidi (Crystals, 2025)
This study reports the synthesis and characterization of CoxNi1−xFe2O4 (x = 0, 0.2, 0.4, 0.6, 0.8, 1) nanoparticles using a co-precipitation method. In this approach, metal ions are precipitated in the presence of a stabilizing agent, which is a common and effective method for nanoparticle preparation. The microstructure and magnetic properties were studied after calcination at 600 °C and heat treatment at 1000 °C. X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy confirmed the formation of a single-phase spinel structure. The average crystallite size, calculated using the (311) diffraction peak and the Scherrer equation, ranged from 13 to 19 nm. Scanning electron microscopy (SEM) showed that the nanoparticles had a spherical morphology. Thermogravimetric and differential thermal analysis (TG-DTA) revealed a three-step weight loss process. Magnetic measurements, including remanent magnetization, saturation magnetization, and coercivity, were performed using a vibrating sample magnetometer (VSM) at room temperature. The replacement of Ni2+ with Co2+ enhanced the magnetic properties, resulting in increased magnetic moment and anisotropy. These effects are attributed to changes in cation distribution, exchange interactions, surface effects, and magnetocrystalline anisotropy. Overall, Co2+ doping improved the magnetic behavior of nickel ferrite, indicating its potential for application in memory devices and magnetic recording media.